PGT-M as A Family Planning Tool for A Couple in Which The Woman Carries A Novel NCAH Variant and A CYP21A2 Variant also Present in Her Husband: A Case Report - Melissa Cavagnoli; Maria Augusta Tamm; Vickie White Loureiro Souza; Ana Cerveró; Taccyanna Mikulski Ali; Juliana Cuzzi; Márcia Riboldi; Maite del Collado (International Journal of Fertility and Sterility)
The hyperandrogenic non-classic congenital adrenal hyperplasia (NCAH) is an autosomal recessive disorder that can lead to a decrease in reproductive function in women due to alterations in hormone levels. Couples in which the woman is affected must investigate the occurrence of the mutation in the partner to assess the possibility of passing on the condition on their offspring. In such cases, genetic counseling plays a crucial role in educating the patient about the risk of having a child with the same disorder. Additionally, assisted reproduction techniques (ART), including preimplantation genetic testing for monogenic diseases (PGT-M), are important to increase the chances of the couple conceiving a healthy child. In this case report, we describe a multidisciplinary approach aimed at achieving two infants who appeared unaffected by the classic form of the condition. The couple carried variants in CYP21A2 gene, and the woman, affected by NCAH, presented a novel variant.